A Systematic Review: How the Implementation of Collaborative Learning in Chemistry? - Hasrilia Beskara; Antuni Wiyarsi (Universitas Pendidikan Ganesha, 2024)
This research aims to determine what chemical materials are commonly used in collaborative learning and what methods/modes/approaches are used in collaborative learning in chemistry classes. The research method used is a systematic literature review (SLR) by analysing relevant research results from the Google Scholar and ERIC databases of 20 articles based on their suitability with the research theme within the last eight years (2016-2023). Through the SLR method, articles are reviewed systematically by following the steps that have been determined. The results of this systematic literature review (SLR) chemical material commonly used in collaborative learning is basic chemistry at the senior high school and university level, then the models/methods/approaches used in collaborative learning are inquiry-based collaborative learning, flipped classroom, and game-based collaborative learning.